An estimate of the TNT-equivalent net explosive quantity (NEQ) of the Beirut port explosion using publicly-available tools and data - Stennett, Christopher; Gaulter, Sally; Akhavan, Jacqueline (Wiley, 2020)
Publicly available video recordings of the explosion in Beirut on August 4, 2020, were examined and from them it was possible, in conjunction with the well‐known Google Maps website, to obtain estimates for the locations of the observers’ cameras with respect to the blast, and estimates for the blast wave arrival time. A publicly‐available blast wave calculator was then used to estimate the size of the explosion in terms of the equivalent quantity of TNT that would produce the same blast wave arrival time at the observers’ distance. This work estimates the Beirut explosion to have been equivalent to 637 tons TNT, with a lower bound estimate of 407 tons and an upper bound estimate of 936 tons
Keywords: Blast; Ammonium nitrate; Beirut